2022
DOI: 10.1038/s41598-022-18469-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular engineering of several butterfly-shaped hole transport materials containing dibenzo[b,d]thiophene core for perovskite photovoltaics

Abstract: Several butterfly-shaped materials composed of dibenzo[b,d]thiophene (DBT) and dibenzo-dithiophene (DBT5) cores were designed as hole transporting materials (HTMs) and their properties were studied by density functional theory (DFT) computations for usage in mesoscopic n-i-p perovskite solar cells (PSCs). To choose suitable HTMs, it was displayed that both of lowest unoccupied molecular orbital (LUMO) and highest occupied molecular orbital (HOMO) energies of molecules were located higher than those of CH3NH3Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…They reported that difunctionalized BTZI‐TPA exhibited a high efficiency of 24.06% due to the better‐aligned energy levels, stronger interaction with uncoordinated Pb 2+ on the perovskite surface, and suppressing charge carrier nonradiative recombination (NRR) and carrier accumulation at the interface of the perovskite/spiro‐OMeTAD [58]. Various butterfly‐shaped materials composed of dibenzodithiophene (DBT5) units were developed by Sarmalek et al, and their properties were studied by density functional theory (DFT) computations for usage as HTMs in mesoscopic n‐i‐p PSCs, achieving the highest PCE of 23.70% for the DBT5‐COOH molecule [59]. Through molecular engineering, new acridine‐based HTMs have been synthesized by replacing the PTZ core and analyzing the effects of peripheral groups on the acridine core.…”
Section: Htms Of 2022mentioning
confidence: 99%
“…They reported that difunctionalized BTZI‐TPA exhibited a high efficiency of 24.06% due to the better‐aligned energy levels, stronger interaction with uncoordinated Pb 2+ on the perovskite surface, and suppressing charge carrier nonradiative recombination (NRR) and carrier accumulation at the interface of the perovskite/spiro‐OMeTAD [58]. Various butterfly‐shaped materials composed of dibenzodithiophene (DBT5) units were developed by Sarmalek et al, and their properties were studied by density functional theory (DFT) computations for usage as HTMs in mesoscopic n‐i‐p PSCs, achieving the highest PCE of 23.70% for the DBT5‐COOH molecule [59]. Through molecular engineering, new acridine‐based HTMs have been synthesized by replacing the PTZ core and analyzing the effects of peripheral groups on the acridine core.…”
Section: Htms Of 2022mentioning
confidence: 99%
“…Eqn (1) and ( 2) were used to calculate the light harvesting efficiency (LHE) and exciton binding energy (E b ) of molecules considered GQDs. [45][46][47]…”
Section: Computational Detailsmentioning
confidence: 99%
“…Eqn (1) and (2) were used to calculate the light harvesting efficiency (LHE) and exciton binding energy ( E b ) of molecules considered GQDs. 45–47 E b = E g − E opt where, f abs max is the oscillator strengths for the maximum absorption peak. E g is defined as the gap energy between the HOMO and LUMO whereas E opt is optical bandgap which is the gap energy between electronic ground state and first excited state.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Among them, thiophene‐based materials have gained considerable attention due to their ability to tune the physical properties of OSC, such as electronic structure, frontier molecular orbital energy levels, optical properties, and charge carrier mobility 12,13 . In particular, benzodithiophene (BDT) and anthradithiophene (ADT) materials were identified as solution‐processable p‐type and n‐type materials in OFETs and OPVs in recent years 14–18 . Masashi Mamada et al synthesized syn and anti‐configurations of ADT and found differences in the physical properties between them 19 .…”
Section: Introductionmentioning
confidence: 99%
“…and anthradithiophene (ADT) materials were identified as solutionprocessable p-type and n-type materials in OFETs and OPVs in recent years. [14][15][16][17][18] Masashi Mamada et al synthesized syn and anticonfigurations of ADT and found differences in the physical properties between them. 19 In particular, the p-channel FET mobility of the anti-ADT derivative (0.42 cm 2 V À1 s À1 ) was higher than that of the syn-ADT (0.12 cm 2 V À1 s À1 ) derivative.…”
mentioning
confidence: 99%